Selecting one story and hiding others: How AYP chooses the portrayal of a school - peter clyde martin (Arizona State University, 2011)
This article discusses how the Adequate Yearly Progress (AYP) accountability mechanism of No Child Left Behind makes use of supposedly objective standardized test scores to describe schools in a certain way when the very same results could serve to draw very different conclusions. Examining the proficiency scores of students from a specific middle school that is determined to be unequivocally failing according to AYP, the article shows how the same data could be used to characterize this school in ways that are more complex and emphasize its possible accomplishments.